2001
DOI: 10.1136/ard.60.5.473
|View full text |Cite
|
Sign up to set email alerts
|

Glandular and extraglandular expression of costimulatory molecules in patients with Sjogren's syndrome

Abstract: Objectives-To investigate the expression and regulation of CD80, CD86, and CD28 costimulatory molecules in sialoadenitis and interstitial nephritis in patients with Sjögren's syndrome (SS). Methods-Expression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
1
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 32 publications
4
54
1
6
Order By: Relevance
“…Interestingly, controversy also exists on the role of apoptosis in patients with Sjögren's syndrome. Although apoptosis has been proposed as an important mechanism in the effector phase of the disease (Kong et al, 1997(Kong et al, , 1998aManganelli et al, 1997;Matsumura et al, 1998), Fas-induced apoptosis was recently reported to be rare in minor salivary glands of patients with Sjögren's sydrome, despite expression of Fas and FasL (Ohlsson et al, 2001). Because fixation and pretreatment of the sections may influence the outcome of the TUNEL staining (Labat-Moleur et al, 1998;Negoescu et al, 1996), careful comparison with the control tissue is critical in the evalutation of TUNELstained sections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, controversy also exists on the role of apoptosis in patients with Sjögren's syndrome. Although apoptosis has been proposed as an important mechanism in the effector phase of the disease (Kong et al, 1997(Kong et al, , 1998aManganelli et al, 1997;Matsumura et al, 1998), Fas-induced apoptosis was recently reported to be rare in minor salivary glands of patients with Sjögren's sydrome, despite expression of Fas and FasL (Ohlsson et al, 2001). Because fixation and pretreatment of the sections may influence the outcome of the TUNEL staining (Labat-Moleur et al, 1998;Negoescu et al, 1996), careful comparison with the control tissue is critical in the evalutation of TUNELstained sections.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, epithelial cells expressed high levels of the apoptosis receptor Fas and the deathinducing molecule Fas ligand (FasL). Infiltrating lymphocytes were shown to express FasL and bcl-2, enabling these cells to induce apoptosis, while themselves being protected from the induction of apoptotic cell death (Kong et al, 1997(Kong et al, , 1998aManganelli et al, 1997;Matsumura et al, 1998).…”
mentioning
confidence: 99%
“…Several studies indicate the involvement of uncontrolled apoptosis in the pathogenesis of SS (27,28,45). Furthermore, enhanced apoptosis has been related to the impairment of secretory function and generation of autoantigens (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported increased ductal epithelial cell turnover and consequent cell death (apoptosis) in the salivary glands of SS patients [36±40], although one study did not corroborate these observations [41]. The combination of a pro-inflammatory microenvironment and the increased exposure of`self-proteins' could lead to immunogenicity thereby explaining the presence in 70±80% of PSS patients of high titres of serum antibodies directed against the Ro (60kd and 52kd) and La (48kd) ribonucleoproteins [33] and other SS associated autoantibodies [34,35].…”
Section: Role Of Epithelial Cellsmentioning
confidence: 99%